Hubungan antara Kecerdasan Emosi dengan Koping pada Gamer - Ummaimah Insyirah Tahali; Esti Hayu Purnamaningsih (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
There are numerous studies about the relationship between emotional intelligence and coping stress. However, there are still a few studies that examined the relationship between those two in the gamer. Hence, the aimed of this study is to empirically examine the relationship between emotional intelligence and coping stress in the gamer. The hypothesis of this study stated that there was a relationship between emotional intelligence and coping stress. Participants of the study were 101 college students who are playing the video game with an age range from 17 to 25. Product moment technique was used to analyze the data. The result of the study showed that there is a significant and positive relationship between emotional intelligence and coping stress (p < 0,001; r = 0,586). Based on this result, the hypothesis was accepted.